2020
DOI: 10.1111/jgh.15019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complications after endoscopic retrograde cholangiopancreatography using a short type double balloon endoscope in patients with altered gastrointestinal anatomy: a single‐center retrospective study of 1,576 procedures

Abstract: Background and AimEndoscopic retrograde cholangiopancreatography (ERCP) using balloon‐assisted endoscope such as double‐balloon endoscope is even effective for patients with surgically altered anatomy. Yet comprehensive studies on complications of ERCP using balloon‐assisted endoscope have not been made. We analyzed the characteristics and the causes of complications of ERCP using double‐balloon endoscope (DB‐ERCP) procedures and aimed to suggest effective managements.MethodsA total of 1576 procedures of DB‐ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Adverse events occur in 5–18% of patients treated with this procedure [ 15 , 20 , 22 , 44 ], and the incidence rate was 5% in the present study. In contrast to conventional ERCP, perforation is one of the most common adverse events for this procedure [ 45 ] and occurs mainly during scope insertion or stone extraction. Immediately noticing the issue and thoroughly performing intraluminal drainage is important, as the situation can sometimes be managed if minor perforation occurs, as shown in one of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events occur in 5–18% of patients treated with this procedure [ 15 , 20 , 22 , 44 ], and the incidence rate was 5% in the present study. In contrast to conventional ERCP, perforation is one of the most common adverse events for this procedure [ 45 ] and occurs mainly during scope insertion or stone extraction. Immediately noticing the issue and thoroughly performing intraluminal drainage is important, as the situation can sometimes be managed if minor perforation occurs, as shown in one of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, ERCP-related adverse events occurred in 25.6% of patients. Previous studies reported the complication rate from 3.5 to 12.4% [ 9 , 11 , 12 , 16 , 18 , 38 40 ]. However, hyperamylasemia was not included in most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…One case of intestinal perforation requiring surgery was included in the report. A single-center large cohort study reported that Billroth II gastrectomy (B-II) and the native papilla were notable risk factors for complications [40]. In that report, especially cases of B-II with an extremely short afferent loop between the gastro-jejunal anastomosis and Treitz ligament, had a risk of perforation because B-II with an extremely short afferent loop tend to receive a strong force while proceeding a scope into the afferent loop.…”
Section: Double Balloon-assisted Ercpmentioning
confidence: 99%